Evaluation of Practice Teachers’ Views on Inclusive Education - A. Agati, Charlene Faye; Caballes, Dennis G. (International Journal of Humanities and Education Development (IJHED), 2023)
This study examined the views of practice teachers toward the inclusion of students with special education needs in the regular classroom. A total of 32 practice teachers from University of the East, College of Education, participated in the research. Mixed-Method was utilized which comprised of participants answering a questionnaire and participating in a focus group discussion. The questionnaire, My Thinking about Inclusion Scale, MTAI, (Stoiber et al., 1998) was utilized for the quantitative part of the research; while, a focus group discussion was conducted for the qualitative part which sought to uncover the perceptions of practice teachers concerning their background and training on inclusive education. Only six of the 32 practice teachers were able to join the focus group discussion. The results revealed that there is no significant difference in the practice teachers’ views on inclusive education between males and females and their degree programs. Findings also showed that practice teachers held similar positive views on inclusion. The responses of the participants in the focus group discussion unveiled that the practice teachers believed they have adequate theoretical knowledge about inclusive education; however, they still require further in-depth training and hands-on involvement and participation in conducting inclusive practices inside classrooms to effectively apply them in the future as they become licensed teachers. They also saw the importance of the support of the government and the cooperation of schools as well as parents and guardians for the successful espousal of inclusive education.